Diplomacy and Architecture: A Relationship of Similarity or Benefit? (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study is part of academic efforts aimed at enhancing communication and collaboration between political science and other fields of study. It focuses on discussing and analyzing the relationship between diplomacy and architecture, with the goal of exploring similarities and points of convergence. Through a comparative approach, the study reveals that there are notable parallels and shared characteristics between diplomacy and architecture, such as their belonging to the political sphere, their emphasis on negotiation and rational persuasion skills, and their shared use of symbols and verbal metaphors, as well as their interaction with public opinion. Additionally, the study highlights that both fields are rooted in scientific knowledge and adhere to rigorous standards. The analysis further shows that the relationship between diplomacy and architecture is characterized by utilitarian exploitation, largely driven by the more dominan
Keywords: Diplomacy; Architecture; Similarity; Benefit; National Identity; Bridges of Communication; Cultural Interaction